How polite are Malaysian undergraduates? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
A growing number of universities and colleges in Japan have started providing information on good manners to their students, especially freshmen (The Sunday Star, 7 March 2010). Many university officials, the report adds, say they have had to train their students in good manners because many do not seem to have much awareness of what behaviour is considered socially acceptable. One of the reasons motivating such efforts is the tight employment situation in the country in recent years.